Callous–Unemotional Traits and Gun Violence: The Unique Role of Maternal Hostility - Nicholas D. Thomson; Sophie L. Kjærvik; Georgia Zacharaki; Abriana M. Gresham; Danielle M. Dick; Kostas A. Fanti (Children)
Background/Objectives: Conduct Disorder (CD) involves persistent behavior violating societal norms and others’ rights. A subgroup of adolescents with CD exhibits callous–unemotional (CU) traits, which are linked to severe antisocial behavior and poorer long-term outcomes. Research suggests parenting plays an important role in the development of CU traits. However, few studies have explored the role of maternal and paternal parenting practices mediating the link between CU traits and violence within the same study. Methods: This study included 222 adolescents with Conduct Disorder (Mage = 15.7, 68% male) and examined whether perceived parental warmth and hostility, measured using the Quality of Parental Relationships, mediated the association between callous–unemotional (CU) traits and youth involvement in violent crime and gun violence, assessed via the Violent Crime Assessment and Gun Violence Questionnaire. Results: Double mediation models showed that only maternal hostility mediated the link between CU traits and violence, while maternal warmth and paternal parenting practices did not. Conclusions: Findings emphasize the role of maternal hostility in exacerbating violence, including gun violence, among adolescents with CD and CU traits.